Pre-coagulated landfill leachate treatment by Electro-oxidation using MMO/Ti, Pt/Ti, and graphite anodes - Guvenc, Senem Yazici; Daniser, Yesim; Can-Guven, Emine; Varank, Gamze; Demir, Ahmet (KOREAN SOC ENVIRONMENTAL ENGINEERS - KSEE, 2023)
In this study, sequential coagulation and electro-oxidation (EO) processes were applied to landfill leachate, which is highly contaminated and complex wastewater. Since the pollutant content of the leachate was too high, the coagulation process (poly aluminum chloride (PAC) as a coagulant) was applied as a pre-treatment to reduce the cost of the EO process. The Box-Behnken design of response surface methodology was used. The color number (CN) removal efficiency estimated by the model under optimum operating conditions was 80.1%, while it was 77.6% in the experimental studies performed under optimum conditions to verify the model conformity. Multi-metal oxide doped Ti (MMO/Ti), Pt doped Ti (Pt/Ti), and graphite were used as anode and stainless steel was used as cathode in the EO process. In the EO process in which Pt/Ti anode was used, chemical oxygen demand (COD),UV 25 4, and CN removal efficiencies were 52.8, 68.1, and 85.6%, respectively under the conditions of applied current 1.25 A and the pH 5. The CN value decreased to 4.2 after the coagulation process and it was 0.6 at the effluent of the EO process.
Keywords: Box-Behnken Design; Coagulation; Color number; Electro-oxidation; Leachate; PAC; ELECTROCHEMICAL OXIDATION; WASTE-WATER; ELECTRODE MATERIALS; OPTIMIZATION; BIODEGRADABILITY; PRETREATMENT; REMOVAL; ELECTROCOAGULATION; ULTRAFILTRATION; FLOCCULATION; Engineering; Environmental Sciences & Ecology